A Stink Bug Euschistus quadrator Rolston (Insecta: Hemiptera: Pentatomidae) - Sara A. Brennan; Joseph Eger; Oscar E. Liburd (EDIS)
Euschistus quadrator, like other stink bugs, is highly polyphagous. It is found on weeds such as clover, vetch and other legumes. It feeds on many different crops, though it is primarily found on cotton, soybeans, and corn. Stink bugs cause injury to various fruits and vegetables by feeding, resulting in significant quality and yield loss. They have piercing-sucking mouthparts and most feed primarily on fruits and seeds. This 5-page fact sheet was written by Sara A. Brennan, Joseph Eger, and Oscar E. Liburd, and published by the UF Department of Entomology and Nematology, June 2012.